Evaluation of feeding practices in the first 12 months of life and nutritional status in an urban setting of a low-resource country: Beira, Mozambique - Calgaro, S.; Avagnina, I.; Vettor, A.; Zin, A.; Girotto, C.; Cebola, B. R.; Muhelo, A. R.; Rosato, I.; Da Dalt, L.; Putoto, G.; Verlato, G. (Frontiers in Nutrition, 2025)
BackgroundStunting is a major public health problem, especially in developing countries. In 2020, 37.5% of children under 5 years in Mozambique were stunted.ObjectivesThis study aims to describe the nutritional practices in a cohort of Mozambican children and to compare them with international recommendations. The secondary objective is to find differences between chronic malnourished (M) versus non-malnourished (NM) children and to detect factors related to malnutrition.MethodsA retrospective study was conducted, including children admitted to Beira Central Hospital in Mozambique, using a questionnaire focusing on early nutritional and complementary feeding (CF) practices. We compared the clinical and feeding characteristics of M and NM children and conducted logistic regression to identify factors associated with chronic malnutrition. Data management was performed using Microsoft Excel Office 365 and statistical analysis with Jamovi (version 2.3).ResultsA total of 103 children were studied (median age: 19 months). Seventy percent were exclusively breastfed, 56% continued breastfeeding during CF, but only 8% breastfed until 2 years of age. The introduction of CF occurred at a median age of 6 months, with the main reason being the baby’s crying. Sugar, salt, and sugary drinks were introduced before 1 year of age. At the time of the survey, 42% of the children’s diets were adequately varied. Statistical analysis showed that M children had statistically significant differences in birth weight percentile, were less likely to be breastfed, and consumed fewer dairy products than NM children. Multivariate logistic regression showed that risk factors for chronic malnutrition included HIV infection in both mother and child (OR: 7.5, 95% CI: 1.6–35.09), unaware initiation of CF (OR: 4.35, 95% CI: 1.45–13.05), and birth weight below the 10th percentile (OR: 3.26, 95% CI: 1.02–10.47). In contrast, early and frequent dairy consumption, as well as ongoing maternal breastfeeding during CF, were identified as protective factors.ConclusionIn our population, the percentage of children with a minimally acceptable diet was low. The use of human milk could be increased, and mistakes in CF practices could be corrected. Our findings highlight the need to raise awareness about the importance of breastfeeding and the timely introduction of appropriately composed CF. Increased attention should be given to children suffering from HIV, with lower birth weights, less breastfeeding, and lower dairy product consumption, in order to prevent malnutrition.